Reliability of reporting by women taking part in a prospective contraceptive study - Vessey, Martin P. (1974)
A prospective study is in progress at 17 family planning clinics to try to provide a balanced view of the beneficial and harmful effects of different methods of contraception. During follow-up, data about pregnancies and their outcome, hospital visits, and changes in contraceptive practices are collected from the participants in the study at routine clinic visits, by postal questionnaire, or by home visiting. Whenever a hospital admission is reported, a copy of the discharge letter or summary is obtained. In the present investigation, the reliability of reporting of pregnancies and their outcome and hospital admissions by 1,915 subjects attending two Scottish clinics was checked by comparing information obtained by the routine survey methods with maternity and hospital inpatient records maintained by the Scottish Home and Health Department. It was found that no births, miscarriages, terminations of pregnancy or admissions for sterilization had been missed in the prospective study while 90% of all other hospital admissions were reported. No evidence was obtained of any important variation in the reliability of reporting between users of different methods of contraception or between different methods of collecting the follow-up information.